Gamified Learning in Islamic Higher Education: A TAM-Based Descriptive Study on Kahoot Usage in EFL - Rezki, Anita; Atikah, Dewi; Tonn-Meller, Horst (IAIN KENDARI, 2025)
This study aims to evaluate students' perceptions of using Kahoot! as a gamified learning tool in the context of English language instruction at IAIN Kendari. Involving 62 students from various academic programs, the research adopts the Technology Acceptance Model (TAM) framework, which includes four main constructs: Perceived Ease of Use, Perceived Usefulness, Attitude Toward Use, and Behavioral Intention to Use. A structured questionnaire, adapted from Suh & Han, 2002 and Davis, 1989, was used to quantitatively measure student perceptions. The findings indicate that the majority of respondents provided positive feedback across all measured constructs. Students reported that Kahoot! was easy to use, improved their learning productivity, and created an enjoyable and interactive classroom environment. Furthermore, most students expressed their intention to continue using Kahoot! in future lessons and to recommend it to peers and lecturers. These results reinforce the effectiveness of gamification, particularly through Kahoot!, in enhancing student engagement, motivation, and academic outcomes. The study recommends broader integration of gamified platforms like Kahoot! to foster dynamic and participatory learning environments in higher education.